Kalimat Tanya dalam Acara "Apa Kabar Indonesia TV One" - Fida Febriningsih (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2013)
The purpose of this research is to analyze the forms and variations of interrogative sentences on “Apa Kabar Indonesia TV One.” The use of sentences on “Apa Kabar Indonesia” is interesting to observe especially the use of interrogative sentences. Since the program is livebroadcast, the use of interrogative sentences occurs more often. Moreover, mostly coming from intellectuals, the resource persons are appropriate to be the object to analyze in this research. to collect the data, the researcher used participatory approach by implementing the technique of tapping, recording and noting. Method of data analysis is descriptive analysis. The result showed that there are four forms and variations used as interrogativesentences on “Apa Kabar Indonesia”. (1) interrogative sentences with interrogative wordslike “what, who, when, why, where, how many/much, how; (2) interrogative sentences with interrogative intonation; (3) interrogative sentences with formative questions like “kan and ya”; (4) interrogative sentences with prefix–kah.